ACTIVITY RATIO: PERFORMANCE INDICATORS THAT DETERMINE PROFITABILITY AND LIQUIDITY - Asiah, Neng; Ayumi, Ayumi; Andriyani, Meli; Sabariddinsah, Sabaruddinsah (Universitas Serang Raya, 2025)
This study aims to analyse the effect of activity ratios, namely accounts receivable turnover, cash turnover, and inventory turnover, on the profitability and liquidity of food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The method used is panel data regression analysis, which utilizes panel data regression analysis with a sample of 22 companies. The research findings indicate that accounts receivable and inventory turnover do not significantly impact profitability and liquidity. But, cash turnover has a significant negative effect on profitability and liquidity. However, when considered simultaneously, receivable turnover, cash turnover and inventory turnover positively influence the companies' liquidity. However, there is no significant effect of receivable turnover, cash turnover and inventory turnover on profitability. These findings provide important insights for company management in formulating better financial management strategies to improve financial performance. Consequently, company management should develop comprehensive financial management strategies that prioritize effective cash and inventory management practices to ensure liquidity while exploring additional factors that can enhance profitability. This study contributes valuable insights into the financial dynamics of the food and beverage sector. It suggests that while activity ratios may not directly boost profits, they play a crucial role in sustaining liquidity, which is essential for operational stability and growth.